2015
DOI: 10.4238/2015.august.14.8
|View full text |Cite
|
Sign up to set email alerts
|

Treating congenital megacolon by transplanting GDNF and GFRα-1 double genetically modified rat bone marrow mesenchymal stem cells

et al.

Abstract: ABSTRACT. We studied the survival and gene expression of glial cell line-derived neurotrophic factor (GDNF) and GDNF receptor a-1 (GFRa-1) double-genetically modified rat bone marrow mesenchymal stem cells (BMSCs) transplanted into the intestinal walls of the rat models with congenital megacolon and determine the feasibility of treatment by transplantation of double-genetically modified rat BMSCs. The rat colorectal intestinal wall nerve plexus was treated with the cationic surface active agent benzalkonium ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…23,24 Most recently, studies have involved the transplantation of stem cells, usually injecting these cells into the diseased bowel after laparotomy. 28 Cheng et al have shown that stem cells can successfully be injected via colonoscopy. 29 This type of procedure could be used to investigate possible treatment strategies in the future.…”
Section: Surgical Models Of Hscrmentioning
confidence: 99%
“…23,24 Most recently, studies have involved the transplantation of stem cells, usually injecting these cells into the diseased bowel after laparotomy. 28 Cheng et al have shown that stem cells can successfully be injected via colonoscopy. 29 This type of procedure could be used to investigate possible treatment strategies in the future.…”
Section: Surgical Models Of Hscrmentioning
confidence: 99%